(RETRACTED) ASSESSING USING TECHNOLOGY: IS ELECTRONIC PORTFOLIO EFFECTIVE TO ASSESS THE SCIENTIFIC LITERACY OF EVOLUTION THEORY - Prastiwi, M S; Kartowagiran, B; Susantini, E; Setiawan, B (Unnes Science Education Journal, 2019)
This paper is retracted by editor due to publication ethics missconducted by author (simultaneously publication in other journal).